The itsy bitsy spider - Trapani, Iza. (Milwaukee : G. Stevens Pub., 1996)
The itsy-bitsy spider encounters a fan, a mouse, a cat, and a rocking chair as she makes her way to the top of a tree to spin her web. Includes music on the last page.
1.3
K-3
Keywords: Children's songs -- Texts; Spiders -- Songs and music; Songs; Spiders -- Songs; Children's songs